2011
DOI: 10.1254/jphs.11r04cp
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Molecular Mechanism and Exploration of Novel Therapeutics for Spinocerebellar Ataxia Caused by Mutant Protein Kinase Cγ

Abstract: Abstract. Spinocerebellar ataxia (SCA) is an inherited neurodegenerative disorder that is characterized by cerebellar atrophy and progressive ataxia and is classified into 31 types by the genetic locus. Recently, missense mutations of PRKCG genes that code protein kinase Cγ (γPKC) have been identified as a causal gene of SCA14. To explore the molecular mechanism of SCA14 pathogenesis, we investigated how mutant γPKC causes the neurodegeneration of cerebellar Purkinje cells (PCs) by expressing mutant γPKC-GFP i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Importantly, the morphological changes correlate with the substantial loss of several PKC isoforms and the decrease in phosphorylation of PKC-downstream targets growth-associated protein-43 (GAP-43) and myristoylated alanine-rich protein kinase C substrate (MARCKS), and they are in agreement with the established role of PKC in the morphology of Purkinje cell neurons. In addition, mutations in PKC cause spinocerebellar ataxia (Chen et al, 2003;Seki et al, 2011), which resembles the motor phenotype of our knockout mice. Thus, our work shows that mTORC2 plays an important role in the brain and that its function in Purkinje cells is cell autonomous.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Importantly, the morphological changes correlate with the substantial loss of several PKC isoforms and the decrease in phosphorylation of PKC-downstream targets growth-associated protein-43 (GAP-43) and myristoylated alanine-rich protein kinase C substrate (MARCKS), and they are in agreement with the established role of PKC in the morphology of Purkinje cell neurons. In addition, mutations in PKC cause spinocerebellar ataxia (Chen et al, 2003;Seki et al, 2011), which resembles the motor phenotype of our knockout mice. Thus, our work shows that mTORC2 plays an important role in the brain and that its function in Purkinje cells is cell autonomous.…”
Section: Introductionsupporting
confidence: 62%
“…Golgi staining was performed by incubating freshly perfused mouse brains in Golgi solution (5% potassium dichromate, 5% potassium chromate, Our findings that several PKC isoforms are almost undetectable in brain lysates of adult RibKO mice are strong in vivo support for the importance of mTORC2 in stabilizing PKCs. Mutations in PKC cause spinocerebellar ataxia (SCA) type 14 (Chen et al, 2003) and as of today, more than 20 causative mutations have been described (Seki et al, 2011). Interestingly, some of the phenotypes described for Purkinje cells expressing those PKC mutants are similar to those observed in RibKO and RiPuKO mice.…”
Section: Histology and Immunohistochemistrymentioning
confidence: 94%
“…We previously characterized the molecular properties of various SCA14 mutant γPKCs (Seki et al, 2005a, 2011). Among these mutants, we selected two mutants (S119P and G128D) that are highly aggregate-prone and cytotoxic, and one mutant (S119F) that does not form aggregates but is cytotoxic to analyze in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Among the PKC subtypes, γPKC is specifically expressed in the central nervous system and is especially abundant in cerebellar PCs (Saito et al, 1988). We previously reported that mutant γPKCs tend to aggregate in cells in culture (Seki et al, 2005a, 2011), causing apoptotic cell death via the impairment of the ubiquitin proteasome system and the induction of ER stress (Seki et al, 2007). Furthermore, we have reported that mutant γPKC induces the improper development of dendrites in cultured PCs, regardless of the presence or absence of its aggregates (Seki et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, several mutations in the C2 Ca 2ϩ -binding domain and kinase domain of PKC␥ have been reported ( Fig. 1A) (12,(15)(16)(17)(18)(19)(20). Our previous study showed that Hsp70 (HSPA1A) was incorporated into aggregates of the C1B domain mutants S119P and G128D and that the knockdown of endogenous Hsp70 exacerbated mutant PKC␥-induced cytotoxicity (14).…”
Section: Incorporation and Up-regulation Of Hsp70 Caused By Aggregatimentioning
confidence: 99%